The Effect of Backrub on Sleep Patterns and Stress Levels in Hypertension Clients - Meirina Meirina; Atik Hodikoh (GLOBAL HEALTH SCIENCE GROUP, 2022)
Currently, non-communicable diseases are increasing, one of which is hypertension. The Household Health Survey (SKRT) report shows that hypertension always ranks as the first cause of death with an increasing percentage of causes of death. In addition to heredity, some hypertensive clients experience unhealthy psychosocial conditions, such as stress and sleep patterns (insomnia). Objective to determine the effect of backrub massage on stress levels and sleep patterns in hypertensive clients in the Bogor City Health Center area Method: This study used a quasi-experimental research design with control group design, with a sample of 60 clients with hypertension. Effect of backrub massage using Independent T test. The results of the Backrub Massage intervention on sleep patterns showed that the T test results were obtained P = 0.07 so there was no significant difference. The results of the Backrub Massage intervention on stress obtained T test results P = 0.008 so that there is a difference in stress before and after the backrub massage. Backrub massage is a non-pharmacological therapy that improves blood circulation and reduces stress levels. The results of this study are very relevant to the theory and results of other studies, namely a decrease in stress levels in hypertensive clients.